LEAVES OF ETHNOMEDICINAL PLANTS BALI, NUTRITIONAL AND ORODENTAL HEALTH - I Gusti Ngurah Alit Wiswasta; I Gusti Ayu Ari Agung (Unmas Press, 2019)
This study is about the use of leaves of Balinese ethnomedicinal plants for nutrition and orodental health which was carried out in some places in Bali. This study was carried for three months with the purpose to know the nutrition, the kind and plants species and the leaves of plants to be used as a traditional treatment for nutrition and orodental health. The study was carried out through literature study, confirmation through interview, and observation; and than to the results of this study described descriptively. The recorded data are names of plant as a local name, general name, and scientific name; nutrition content, the leaves of plants to be useful as a traditional nutrition to treat the orodental health. Most parts of the plants used for the traditional orodental nutrition and health are leaves of the plants which most commonly consumed is Piper betle, Saurophus androgyros, Centella asiatica, Jatropha curcas, Pithecelebium dulce, Erythrina orientalis, Hibiscus tiliaceus. The research found that 11 species of leaves of ethnomedicinal plants usually can be used for medicinal treatment for the orodental diseases. The nutritional and antioxidant content of the leaves of the plants for orodental health are chlorophyll, vitamin A, B, C, and mineral Mg, K, Ca, Fe, P.